PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA DENGAN FASILITAS KERJA SEBAGAI VARIABEL MODERASI (Studi pada ASN Inspektorat Kabupaten Ponorogo) - ekasari, wiwik (Universitas Slamet Riyadi, 2020)
Basically, many factors affect the work motivation of an employee in a company or an organization. First is the organizational culture which is the core thing for an organization or company, because it will always be related to life in the company. Many things determine the culture of the organization itself: there is a work team, leadership, organizational character and administrative processes that apply so this becomes very important because in it there are habits and norms that will continue to be followed by members of the organization and will strengthen the organization and accommodate organizational goals. This study aims to determine the effect of organizational culture, job satisfaction and work facilities on work motivation in the Inspectorate of Ponorogo Regency. Data collection was carried out through a questionnaire with a purporsive sampling method. The data analysis technique is done by using multiple regression analysis methods. Organizational culture influences work motivation in Ponorogo Regency Inspectorate. Furthermore, job satisfaction affects work motivation at the Ponorogo Regency Inspectorate. Work facilities affect work motivation in the Ponorogo Regency Inspectorate. known the magnitude of the effect of the variable job satisfaction on work motivation is 0,677 or 67,7%. After interacting with the moderation variable in this case the work facilities, the r square value in accordance with the results of the study amounted to 0,705 or 70,5%, an increase of 2,8%. Based on the results of these comparisons, it can be concluded that the fifth hypothesis is accepted, namely that work facilities moderate job satisfaction in influencing work motivation in the Ponorogo Regency Inspectorate.Â Keywords: Influence, Organizational Culture, Job Satisfaction, Work Facilities, Work Motivation